Peningkatan Inovasi Guru Melalui Kepemimpinan Transformasional Kepala Sekolah Dan Motivasi Berprestasi - Andi Supriyana; Bibin Rubini; Herfina Herfina (JURNAL MANAJEMEN PENDIDIKAN, 2022)
Improving Teacher Innovation through Transformational Leadership of School Principles and Achievement MotivationThis study aims to formulate concrete efforts in order to improve teacher innovation through a study on the relationship between; 1) transformational leadership and teacher innovation, 2) achievement motivation and teacher innovation, 3) transformational leadership and achievement motivation together with teacher innovation. This research was carried out at a private junior high school in Bogor Tengah District, Bogor City. This study was taken in correlational research using a quantitative approach. The population in this study were all permanent teachers of the Bogor City Private Junior High School foundation; 165 of 15 private junior high schools. The research sample was 117 people taken by proportional random sampling technique. The results of the study at a significant level of 5% showed that: 1) transformational leadership had a positive effect on teacher innovation where the correlation coefficient was ry1 = 0.53 and transformational leadership contributed 27.8% to teacher innovation, 2) achievement motivation had a positive effect on innovation teachers where the correlation coefficient was ry2 = 0.24 and achievement motivation contributed 5.9% to teacher innovation, 3) transformational leadership and achievement motivation together with teacher innovation as indicated by the correlation coefficient ry12 = 0.54 and transformational leadership and achievement motivation simultaneously contributed 29.1% to teacher innovation. The conclusion is that the higher the level of transformational leadership and achievement motivation, the higher the innovation of the teacher.